Periodization Model for Costa Rican Taekwondo Athletes - Carazo Vargas, Pedro (2015)
The purpose of this article is to describe the conditioning of elite taekwondo competitors based on the block-periodized training model. this model of periodization has been used by the Costa Rican National Taekwondo Team and guided their physical preparation for international competitions including the Beijing 2008 and London 2012 Olympic Games. examples of drills performed are presented for a macrocycle of preparation aimed to develop physical and technical qualities required for successful preparation in this combat sport.